A Taiwanese Boy With Congenital Generalized Lipodystrophy Caused by Homozygous Ile262fs Mutation in the BSCL2 Gene - Hsiu-Hui Huang; Tai-Heng Chen; Hui-Pin Hsiao; Chia-Tsuan Huang; Cheng-Chu Wang; Ya-Huei Shiau; Mei-Chyn Chao (Kaohsiung Journal of Medical Sciences, 2010)
Congenital generalized lipodystrophy (CGL) is a rare autosomal recessive disease that is characterized by a near-complete absence of adipose tissue from birth or early infancy. Mutations in the BSCL2 gene are known to result in CGL2, a more severe phenotype than CGL1, with earlier onset, more extensive fat loss and biochemical changes, more severe intellectual impairment, and more severe cardiomyopathy. We report a 3-month-old Taiwanese boy with initial presentation of a lack of subcutaneous fat, prominent musculature, generalized eruptive xanthomas, and extreme hypertriglyceridemia. Absence of mechanical adipose tissue in the orbits and scalp was revealed by head magnetic resonance imaging. Hepatomegaly was noticed, and histological examination of a liver biopsy specimen suggested severe hepatic steatosis and periportal necrosis. However, echocardiography indicated no sign of cardiomyopathy and he showed no distinct intellectual impairment that interfered with daily life. About 1 year later, abdominal computed tomography revealed enlargement of kidneys. He had a homozygous insertion of a nucleotide, 783insG (Ile262fs mutation), in exon 7 of the BSCL2 gene. We reviewed the genotype of CGL cases from Japan, India, China and Taiwan, and found that BSCL2 is a major causative gene for CGL in Asian.